Alveolar macrophages depletion affects the ability of Dolosigranulum pigrum 040417 to protect infant mice against pneumococcal infection - Raya Tonetti, María Fernanda (2021)
Previously, we demonstrated that the nasal administration of the respiratory commensal bacterium Dolosigranulum pigrum 040417 (Dp04) to infant mice differentially modulates the respiratory immune response triggered by Toll-like receptor (TLR)-2 activation, increasing the resistance to Streptococcus pneumoniae (Sp) infection. The nasal priming with Dp04 reduced pneumococcal counts in lung and blood and diminished the levels of lung injury biomarkers. In this work, we aimed to characterize the role of alveolar macrophages (AM) on the immunomodulatory properties of Dp04 in the context of pneumococcal infection. In the first set of experiments, mice were nasally stimulated with Dp04 (108 cells/mouse/day) for 5 consecutive days and then challenged with 106 CFU of Sp. Variations in numbers and functionality of resident AM in broncho-alveolar lavage (BAL) samples were evaluated. The number of activated CD11c+SiglecF+MHC-IIhi AM was significantly increased after Sp challenge in mice primed with Dp04 than in controls (p<0.05). Furthermore, AM obtained from Dp04-treated mice produced in vitro higher levels of IFN-β and IFN-γ, as well as IL-10 and IL-27 compared to the control group (p<0.05). In a second set of experiments, AM were depleted using liposomes containing clodronate (CLP) before the stimulation of with Dp04. The CLP treatment significantly affected the ability of Dp04 to reduce pneumococcal cell counts, as well as lung injury biomarkers. In addition, AM depletion impaired the capacity of Dp04 to differentially modulate the cytokine profile in the respiratory tract. The ability of Dp04 to increase the levels of BAL IFN-γ, IL-10 and IL-27 in response to Sp infection was abolished when AM were depleted by CLP (p<0.05). This results show for the first time that AM have a relevant role in the immunomodulatory effect of Dp04. Our results also mark a significant advance in the positioning of Dp04 as a next-generation probiotic for the respiratory tract.